What Fascism? : Lukács, Heidegger, Schmitt, and National Socialism (World Marxist Review, 2025)
This paper considers Carl Schmitt’s and Martin Heidegger’s Nazism and their apologetic receptions among the broadly post-structuralist intellectual Left, as a critical illustration of the unsettling prescience of Lukács’ often-maligned 1950s analyses of irrationalism in theory, and its historical connections to fascism. It does this by positioning Lukács’ Marxian position in pointed contrast to the more recent apologetics that have widely surrounded these thinkers’ Nazism. We revisit Lukács’ reading of Heidegger in DR, and, his reading of Schmitt. These parts show how Lukács’ critiques were able already in the early 1950s to lucidly diagnose the two thinkers’ Nazism, by building upon an historically materialist analysis of the politico-economic factors in later 19th century-early 20th century Germany, and situating Heidegger and Schmitt within a lineage of German irrationalism which responded to these factors. We contend that the predominant responses from poststructuralist-influenced thinkers to the disclosures of the political stances of Schmitt and Heidegger, far from allowing critical thinkers to adequately conceive and combat the ideas underlying National Socialism and kindred political forms today, illustrate what Lukács in DR described as an immanent tendency within irrationalism towards apologetics, a narrowing of scope, and a decline in scholarly standards, whose prospects for the socialist Left are at best ambivalent.